(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Bihar has emerged as unimportant centre for horticultural production in the country. Nevertheless, producefrom Bihar is not a dominant part of India’s trade horticultural trade basket. The article examines the issues relating toexport of major horticultural products of Bihar using information collected through sample survey conducted inMuzaffarpur district of Bihar. It is seen that farmers are inclined to take up horticulture given the high returns in a smallertime-frame. However a umber of infrastructural and logistical constraints prevent realisation of large returns. The articleexamines some of these issues using information collected from secondary sources like newspaper articles, journals andgovernment reports as well as information collected during author’s research.